The Charterhouse of Bruges - Jan van Eyck, Petrus Christus, and Jan Vos - Capron, Emma (The Frick Collection, 2018)
"At the heart of the exhibition is the reunion...for the first time in more than twenty years and the second time in their history...of the Exeter Madonna and the Frick Virgin, Jan Vos's two surviving commissions. Complementing them will be a selection of objects that place them in their rich context. Leaving questions of attribution aside, the exhibition will focus on the works' patronage, function, reception, and spiritual environment."